Diagnostic Accuracy of Advanced Imaging in Cardiac Sarcoidosis - Divakaran, Sanjay; Stewart, Garrick C; Lakdawala, Neal K; Padera, Robert F; Zhou, Wunan; Desai, Akshay S; Givertz, Michael M; Mehra, Mandeep R; Kwong, Raymond Y; Hedgire, Sandeep S; Ghoshhajra, Brian B; Taqueti, Viviany R; et al. (Circulation. Cardiovascular imaging, 2019)
Background The diagnostic yield of cardiac sarcoidosis (CS) by endomyocardial biopsy is limited. Fluorodeoxyglucose (FDG) positron emission tomography (PET) and cardiac magnetic resonance imaging (MRI) may facilitate noninvasive diagnosis, but the accuracy of this approach is not well defined. We aimed to correlate findings from FDG PET and cardiac MRI with histological findings from explanted hearts of patients who underwent cardiac transplantation. Methods We analyzed the explanted heart histology for all patients who underwent cardiac transplant at our center from April 2008 to July 2018 and had pretransplant FDG PET (n=18) or cardiac MRI (n=31). The likelihood of CS based on FDG PET or cardiac MRI was categorized in a blinded fashion using a previously published method. RESULTS: Using a CS probable cutoff for FDG PET resulted in a sensitivity of 100.0% (95% CI, 54.1%-100.0%) and a specificity of 33.3% (95% CI, 9.9%-65.1%). Three of the 9 CS probable by FDG PET cases were found to be arrhythmogenic cardiomyopathy. The test characteristics of cardiac MRI are more challenging to comment on using our data as there was only one confirmed case of CS on post-transplant histological assessment. Of the 8 CS highly probable or probable cases by cardiac MRI, 3 were found to be dilated cardiomyopathy, and 2 were found to be end-stage hypertrophic cardiomyopathy. Conclusions FDG PET and cardiac MRI can help facilitate the diagnosis of CS in patients with advanced heart failure with a high degree of sensitivity but lower specificity.